Nursing Care of Hypertension in the Elderly with a Focus on Study of Activity Intolerance in Dr. R. Soetijono Blora Hospital - Warijan Warijan; Teguh Wahyudi; Yuni Astuti; Risma Dwi Rahayu (Jurnal Studi Keperawatan, 2021)
With the increasing life expectancy of the Indonesian population, it can be estimated that the incidence of degenerative diseases is increasing. Based on basic health research, hypertension is the most degenerative disease in the elderly with a prevalence of 57.6% at ages 65-74 years and 63.8% aged75 years. Hypertension causes the elderly to experience fatigue or weakness.The purpose of this study is to describe the nursing care of hypertension in the elderly with a focus on activity intolerance studies. This research design uses a descriptive research approach. The subjects used were 2 patients who had inclusion criteria; individuals with hypertension aged 60-90 years and willing to be the subject of case studies, exclusion criteria; individuals are not willing to be the subject of research and have special handling diseases. Data collection was carried out by interview, observation, physical examination and nursing documentation.The results were obtained through nursing care in both patients, where both patients had hypertension with a diagnosis of activity intolerance with different levels of activity independence. So given the nursing action physical activity therapy according to patient tolerance. Conclusions from the results of the study are that it is important to choose and provide the stages of activity needs, education and pay attention to the safety of the elderly.Suggestions submitted, the hospital should prevent accidents in elderly patients. For nurses, education should improve the fulfillment of the activity needs of patients and families.